2022
DOI: 10.1111/aec.13235
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive systems of woody species in vereda are distributed according to the life form and habitat occurrence

Abstract: In Cerrado humid areas, veredas are considered as hygrophilous communities, with an herbaceous/shrub stratum in open areas and an arboreal stratum in forest areas. We identified the sexual and reproductive systems of woody species, and the distribution of these systems among the different habitats and plants habits in this ecosystem. We investigated whether the occurrence of sexual and reproductive systems may be related to ecological and/or evolutionary factors and if hermaphroditism predominates in open area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
(219 reference statements)
0
2
0
Order By: Relevance
“…Matias et al (2022) found localized abiotic factors, such as cation exchange capacity, have a strong influence on growth‐form composition. In Minas Gerais, South‐eastern Brazil, Silva et al (2022) assessed the life form and habitat occurrence that influence vereda (hygrophilous communities) reproductive systems. In open areas, trees exhibited dioecy, and shrubs were primarily hermaphroditic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Matias et al (2022) found localized abiotic factors, such as cation exchange capacity, have a strong influence on growth‐form composition. In Minas Gerais, South‐eastern Brazil, Silva et al (2022) assessed the life form and habitat occurrence that influence vereda (hygrophilous communities) reproductive systems. In open areas, trees exhibited dioecy, and shrubs were primarily hermaphroditic.…”
mentioning
confidence: 99%
“…In open areas, trees exhibited dioecy, and shrubs were primarily hermaphroditic. Overall, shrubs and sub shrubs were autogamous and apomictic species but were not influenced by habitat (Silva et al, 2022). The influence of fire on New Zealand restaid bog peat seed banks from Koputai Bog was assessed by Wilson et al (2022).…”
mentioning
confidence: 99%